OPTIMIZATION OF FACS SORTING FOR THE IMPROVEMENT OF LIVESTOCK SEMEN QUALITY - Vasicek, Jaromir; Svoradova, Andrea; Balazi, Andrej; Jurcik, Rastislav; Machac, Marian; Ostro, Alexander; Chrenek, Peter (Journal of microbiology, biotechnology and food sciences, 2021)
Fluorescence-activated cell sorting (FACS) of spermatozoa was mainly used for sex sorting. Recently, FACS has been used to eliminate DNA-damaged human spermatozoa using YO-PRO-1 staining. Fragmentation of sperm DNA is considered as one of the reasons of male infertility. Moreover, YO-PRO-1 can effectively mark apoptotic as well as dead spermatozoa. Till now, only two FACS instruments were used for the spermatozoa sorting. However, both of them are not more commercially available from different reasons. In this study, we used novel FACSMelody Cell Sorter for the elimination of apoptotic and dead cells from the rabbit and ram semen samples in order to improve their overall quality. Briefly, semen samples were stained using YO-PRO-1 dye (apoptotic and dead cells) and/or propidium iodide (PI; only dead cells). Three different sorting experiments were performed: E1 – YO-PRO-1 and PI stained rabbit sperm cells were sorted into the tubes containing 1 ml of PBS; E2 – PI stained rabbit sperm cells were sorted into tubes that were washed with FBS prior adding PBS; and E3 – YO-PRO-1 and PI stained ram sperm cells were sorted into tubes washed with FBS prior adding PBS. As a sheath fluid sterile PBS was used. All samples, control (before sorting), negatively and positively sorted fractions, were analysed using CASA for motility assessment. Moreover, all sorted samples were re-stained with PI for viability assessment. In conclusion, elimination of dead (PI+) sperm from rabbit samples might improve their quality, since their progressive motility increased significantly (P<0.001) after sorting from 40 to 65%. However, ram spermatozoa seem to be sensitive to sorting procedure thus further optimisation of this procedure is required.